2022
DOI: 10.31080/asvs.2022.04.0482
|View full text |Cite
|
Sign up to set email alerts
|

On Farm Diagnostics and Preventive Measures for Mastitis in Dairy Bovines Category: Review Article

Abstract: Mastitis is defined as a multi-etiological disease that causes inflammation of the udder. It is one of the costliest production diseases accounting for an economic loss of 100 trillion US dollars globally and approximately Rs. 7165.51 crores in India. The incidence and prevalence rate is higher in sub-clinical mastitis than clinical mastitis in most herds throughout the World. It affects the quantity and quality of milk as well as the udder health of dairy animals. Poor sanitation and hygienic measures account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A chaff cutter is the first stage of mechanization of feeding where 30-40 percent savings in the cost of fodder has been observed. 18 found out that chaffing machines alone can reduce feed costs by 8 percent. Mixing the ingredients and dispersing them into mangers can be done with the help of Total Mixed Ration (TMR) mixing wagons.…”
Section: Mechanization In Commercial Dairy Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A chaff cutter is the first stage of mechanization of feeding where 30-40 percent savings in the cost of fodder has been observed. 18 found out that chaffing machines alone can reduce feed costs by 8 percent. Mixing the ingredients and dispersing them into mangers can be done with the help of Total Mixed Ration (TMR) mixing wagons.…”
Section: Mechanization In Commercial Dairy Farmsmentioning
confidence: 99%
“…So, investment towards mechanization in smaller farms is a challenging factor that may affect profitability. 18 reported that primary farms require one labour for average 7.6 cows, but in farms with automatic equipment for milking, transport and forage chopping, a labour can manage 24.3 heads of cows. The specialized farms with less herd size are getting more profit.…”
Section: Mechanization In Commercial Dairy Farmsmentioning
confidence: 99%